PEMODELAN UMUR FATIK ALAT PENGANGKAT ROKET KAPASITAS 20 TON MENGGUNAKAN ANSYS WORKBENCH - LASINTA ARI NENDRA WIBAWA (Jurnal Turbulen, 2019)
A rocket lifting device is a tool designed to facilitate the rocket assembly process. The device is mounted on a crane and is equipped with two webbing slings placed at the bottom. The study examines the fatigue life prediction of rocket lifting device using the finite element method. The design of rocket lifting device using Autodesk Inventor Professional 2017, while finite element analysis using Ansys Workbench. It is subjected to a 20-ton load with a fully-reserved type of loading. The fatigue life prediction using the Gerber mean stress theory. The material for the rocket lifting device is Aluminum alloy. The simulation results show that the rocket lifting device has a minimum fatigue life of up to 4.17 x 107 cycles with a minimum safety factor of 1.14. Keywords: aluminum alloy, ansys, rocket lifting defice, finite element method, fatigue life prediction